A study on the maturation of procyclic Trypanosoma brucei brucei in Glossina morsitans centralis and G. brevipalpis - Moloo, S.K.; Kabata, J.M.; Sabwa, C.L. (Wiley, 1994)
Abstract. Teneral Glossina morsitans centralis and G. brevipalpis were fed in vitro upon medium containing procyclic Trypanosoma brucei brucei derived from the midguts of G. m. centralis or G. brevipalpis which had immature trypanosome infections. The tsetse were then maintained on rabbits and, on day 31, were dissected to determine the infection rates. In G. m. centralis the midgut and salivary gland infection rates by T. b. brucei were 46.0% and 27.0% with procyclic trypanosomes from G. m. centralis, and 45.4% and 24.7% with procyclic trypanosomes from G. brevipalpis, respectively. In G. brevipalpis the rates were 20.2% and 0.0% with procyclic trypanosomes from G. m. centralis, and 28.0% and 0.0% with procyclic trypanosomes from G. brevipalpis, respectively. Teneral G. m. centralis and G. brevipalpis were also fed similarly upon procyclic T. b. brucei derived from G.m.centralis or G. brevipalpis on day 31 of infection, the former tsetse species had mature infections while the latter were without infections in the salivary glands. In G.m.centralis the infection rates in the midgut and salivary glands were 48.9% and 17.0%, and 38.0% and 17.0% when fed on procyclic trypanosomes from G.m.centralis and G. brevipalpis, respectively. In G. brevipalpis the rates were 21.5% and 0.0%, and 10.7% and 0.0% with procyclic trypanosomes of G.m.centralis and G. brevipalpis origin, respectively. Thus, procyclic T. b. brucei from susceptible G.m.centralis could not complete cyclical development in refractory G. brevipalpis, whereas those from G. brevipalpis developed to metatrypanosomes in the salivary glands of G.m.centralis. Teneral and 15‐day‐old non‐teneral G.m.centralis were fed in vitro upon heparinized goat's blood containing T. b. brucei bloodstream trypomastigotes, or upon medium containing procyclic T. b. brucei derived from G.m.centralis with mature infections. On day 31 their infection rates were determined. The infection rates by T. b. brucei in the midgut and salivary glands of G.m.centralis fed on the infected blood were 70.4% and 40.4% when fed as teneral tsetse, as against 15.3% and 4.0% when fed as non‐teneral tsetse. Those tsetse which were fed on the medium containing procyclic trypanosomes showed rates of 50.0% and 25.6%, as against 11.6% and 2.5%, respectively. It would appear, therefore, that maturation of T. b. brucei in tsetse is probably not determined simply by an interaction between lectin and procyclic trypanosomes in the midgut of non‐teneral tsetse, but it is the result of a complex interaction between many interrelated physiological factors of both the trypanosome and the tsetse vector.